2019
DOI: 10.1186/s13063-019-3813-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electroacupuncture frequencies on chronic low back pain in older adults: triple-blind, 12-months protocol for a randomized controlled trial

Abstract: BackgroundLow back pain (LBP) is the most frequent complaint in clinical practice. Electroacupuncture treatment may be effective; however, the supporting evidence is still limited, especially in older adults.ObjectiveThe current study is a randomized controlled trial that aims to evaluate the clinical efficacy of electroacupuncture in older adults with LBP.MethodsA five-arm randomized controlled trial with patients and evaluators blinded to the group allocation. A total of 125 participants with non-specific LB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Electroacupuncture stimulation can cause needle sensory conduction, which can alleviate the compression of the vertebral artery and cervical sympathetic nerve to a greater extent and relieve the current situation of obstructed blood flow in the vertebrobasilar artery. On the other hand, electroacupuncture treatment can improve the microcirculatory status, regulate capillary permeability, and increase tissue oxygenation and blood flow operation [ 22 ]. Therefore, electroacupuncture treatment can significantly reduce the symptoms of vertigo.…”
Section: Discussionmentioning
confidence: 99%
“…Electroacupuncture stimulation can cause needle sensory conduction, which can alleviate the compression of the vertebral artery and cervical sympathetic nerve to a greater extent and relieve the current situation of obstructed blood flow in the vertebrobasilar artery. On the other hand, electroacupuncture treatment can improve the microcirculatory status, regulate capillary permeability, and increase tissue oxygenation and blood flow operation [ 22 ]. Therefore, electroacupuncture treatment can significantly reduce the symptoms of vertigo.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical studies have confirmed that EA exhibits specific antinociceptive effects. 2 , 32 In clinic practice, varying frequencies of EA are utilized to enhance analgesic effect. It has been suggested that the low frequency (2 Hz) EA is mainly mediated by the hypothalamic arcuate nucleus, whereas the high frequency (100 Hz) is integrated by different nucleus of the brainstem.…”
Section: Discussionmentioning
confidence: 99%
“…EA involves the application of electrical stimulation along with acupuncture stimulation, and is widely used in clinical practice to relieve acute or chronic pain. [ 1 ] It has been used in the treatment of neck pain, [ 19 ] low back pain, [ 20 ] and neuropathic pain, [ 21 ] and is a method frequently used in the treatment of degenerative KOA. In Korea, EA is recommended as one of the most common treatments for knee pain in clinical practice.…”
Section: Introductionmentioning
confidence: 99%